Evaluasi Penyelenggaraan Pemilu Terkait Regulasi Pencoretan/Pembenaran Hasil Penghitungan Suara - Silalahi, Wilma (MORALITY: Jurnal Ilmu Hukum, 2024)
The implementation of the 2024 general elections poses ongoing challenges for organizers, with various issues and disputes arising as key considerations. While such disputes are an inevitable aspect of elections, evaluating election administration becomes essential. This study focuses on the evaluation of election administration in relation to regulations on vote count annulments and corrections. The objective is not to imply that the 2024 elections were poorly managed but to explore how election regulations provide legal certainty to the Indonesian populace, given that elections are the nation’s largest democratic event. Utilizing normative legal research, this study emphasizes that laws and regulations should align with the principles of Pancasila and the 1945 Constitution, which are the highest legal authorities in Indonesia. Additionally, it examines the implications of corrections made to vote count records. An evaluation of election administration, particularly concerning vote count annulments and corrections, is vital. Moreover, existing regulations must adapt to the evolving constitutional framework and be responsive to the needs of Indonesian society and the nation.